Identifying and analysing the drivers of heterogeneity among ecosystem builder accelerators. (18th November 2018) - Prexl, Katja‐Maria; Hubert, Marco; Beck, Susanne; Heiden, Christian; Prügl, Reinhard
Abstract : In response to convergent and dynamic market developments, established firms use corporate accelerators to open their innovation processes to start‐ups. Among different accelerator themes, the ecosystem builder theme introduced by recent research plays a crucial role in furthering our understanding of the heterogeneity of accelerators due to its broad objectives. By interviewing 20 leading experts from 16 German corporate accelerators, we first identify heterogeneity among different ecosystem builder accelerators based on the differences in the process of selection, business support, and graduation. Second, we further structure the observed heterogeneity by depicting five different ecosystem builder accelerator types instead of a single ecosystem builder theme. These ecosystem builder accelerator types show important differences and similarities in terms of strategies, design elements, and processes within each of the process steps. Our findings hold meaningful research and managerial implications by providing (1) a consistent and systematic conceptual understanding about ecosystem builder accelerators, their strategies, design elements, and processes and (2) guidance to design and position ecosystem builder accelerators with regard to a long‐term corporate strategy.